Effective Targeting of Raf-1 and Its Associated Autophagy by Novel Extracted Peptide for Treating Breast Cancer Cells - El-Fadl, Hebatullah M. Abou; Hagag, Naglaa M.; El-Shafei, Reham A.; Khayri, Mohamed H.; El-Gedawy, Gamalat; Maksoud, Ahmed I. Abd El; Mohamed, Doaa D.; Mohamed, Dalia D.; El Halfawy, Ibrahim; Khoder, Ahmed I.; Elawdan, Khaled A.; Elshal, Mohamed F.; et al. (Frontiers in Oncology, 2021)
Breast cancer is one of the most common causes of death in women worldwide, as well as its harmful influence on their psychological state during therapy. Multikinase inhibitors have become effective drugs for treating a variety of cancer diseases such as breast cancer. A purified short peptide (H-P) was isolated from the natural honey and tested for its potential regulatory role in breast cancer cells compared with the effectiveness of the anticancer drug, Sorafenib (SOR), using MCF-7, EFM-19, and MC7-10A cell lines. Furthermore, we investigated the direct connection between Raf-1 activation and cellular autophagy as potential targets of SOR and H-P extract using RNA interference. Interestingly, the treatment with H-P showed competitive regulation of phosphorylated Raf-1, MEK1/2, and matched autophagy-related LC3B without any detectable toxic effects in the non-tumorigenic epithelial cells. Unlike SOR, the regulation of Raf-1 protein and autophagic machinery by the novel H-P extract showed neglected levels of the released proinflammatory cytokine. This regulation of cytokine secretion by H-P resulted in decreasing the expression level of the transcription factor NF-kB in treated cells. Moreover, the transfection of MCF-7 cells with siRNA antagonist Raf-1 expression markedly reduced the expression of LC3B while increased the expression of NF-kB1 and NF-kB2, indicating the potential cross-link between Raf-1, autophagy, and NF-kB effector. Collectively, these findings suggest that H-P mediated Raf-1, MEK1/2, LC3B, and NF-kB provides a novel and efficacious multikinase inhibitor for treating breast cancer without detectable cytotoxic effects.